1996
DOI: 10.1128/jb.178.2.456-461.1996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the surface-exposed lipids on the cell envelopes of Mycobacterium tuberculosis and other mycobacterial species

Abstract: The surface-exposed lipids of Mycobacterium tuberculosis, Mycobacterium avium, Mycobacterium kansasii, Mycobacterium gastri, Mycobacterium smegmatis, and Mycobacterium aurum were isolated by gentle mechanical treatment of cells with glass beads. Analysis of the exposed lipids demonstrated a selective location of classes of ubiquitous lipids on the surfaces of mycobacteria. While phosphatidylethanolamine and phosphatidylinositol mannosides were exposed in all the species examined, dimycoloyl trehalose (''cord f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
238
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(259 citation statements)
references
References 53 publications
21
238
0
Order By: Relevance
“…These long chain components are thought to intercalate with the mycolic acid layer by hydrophobic interaction resulting in the exposition of the more polar groups of the free lipids to the hydrophilic exterior. Recently, Ortalo-Magné et al (25) identified the surface-exposed lipids of several mycobacterial species. They isolated the lipids of Mycobacterium tuberculosis, Mycobacterium avium, Mycobacterium kansasii, Mycobacterium gastri, Mycobacterium smegmatis, and Mycobacterium aurum by gently treating the cells with glass beads thereby demonstrating a selective location of classes of ubiquitous lipids on the surface of mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These long chain components are thought to intercalate with the mycolic acid layer by hydrophobic interaction resulting in the exposition of the more polar groups of the free lipids to the hydrophilic exterior. Recently, Ortalo-Magné et al (25) identified the surface-exposed lipids of several mycobacterial species. They isolated the lipids of Mycobacterium tuberculosis, Mycobacterium avium, Mycobacterium kansasii, Mycobacterium gastri, Mycobacterium smegmatis, and Mycobacterium aurum by gently treating the cells with glass beads thereby demonstrating a selective location of classes of ubiquitous lipids on the surface of mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Monomycolyl trehaloses and triacylglycerides were exposed in M. avium and M. smegmatis but not in other mycobacterial species studied so far. Phenolic glycolipids, dimycocerosates of phtiocerols and lipooligosaccharides were identified at the surface of M. tuberculosis (Canetti), M. kansasii, and M. gastri, whereas glycopeptidolipids were identified in the outermost layer of M. avium and M. smegmatis (25). However, a glycosylated N-acyl peptide on the cell surface of G. hydrophobica has so far not been isolated as a constituent of a cell envelope.…”
Section: Discussionmentioning
confidence: 99%
“…Although these major cell wall constituents are relatively well described, their three-dimensional distribution remains poorly understood and somewhat controversial [10,16]. In particular, while a large proportion of lipoarabinomannan (LAM) and mannosylated phosphatidyl inositol (LM and PIMs) are proposed to be anchored into the cell membrane via their lipidic portion, they are also known to be present in the outermost portion of the envelope, which allows them to interact with the immune system [23,26]. Thus, it is still unclear whether hydrophobic mycolic acids are present in the form of a continuous, outermost layer on the surface or whether hydrophilic polysaccharides, particularly LAMs, are embedded in this layer [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Probe sonication resulted in effective disaggregation of M. parafortuitum and M. immunogenum based on EFM and FCM quantification, giving a good linear correlation between both enumeration methods (Chang et al, 2004). It is plausible that the components in the semisynthetic MWF had prevented the 62 CHANG AND ADRIAENS mycobacterial cells from reaggregating (Calleja, 1984;Ortalo-Magné et al, 1996). Optical interference due to MWF matrices has been successfully overcome by adding low-polarity solvents (Chang et al, 2004(Chang et al, , 2005.…”
Section: Pretreatment and Amendment Of M Immunogenum In Mwfsmentioning
confidence: 99%
“…Traditional immunofluorescence (IF) has been applied to detect mycobacteria in clinical matrices (Ortalo-Magné et al, 1996;Yi et al, 1998) and also in metalworking fluids (Chang et al, 2005). However, it has been shown that the recovery rate in IF was relatively low (Chang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%